2020
DOI: 10.1002/er.5940
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic optimization of thermoelectric performance in cementitious composites by lithium carbonate and carbon nanotubes

Abstract: Summary Thermoelectric cement‐based composite materials can convert the temperature difference between indoor and outdoor into electrical energy in summer. And the energy can be reversed to remove ice and snow on the pavement in winter. However, how to improve its thermoelectric conversion efficiency is the primary technical problem currently facing. Carbon nanotubes are often used as a container for their unique tubular structure. In this study, lithium acetate was filled in carbon nanotubes to obtain lithium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The samples prepared with borondoped carbon nanotubes have the highest ZT value, 3.3 times the 5.0 wt% content of the samples prepared by the original CNTs. The higher ZT values of boron-doped CNTs cement matrix composites when the content of CNTs, [13,14,29] EG, [15,83] and reduced graphene oxide (RGO) [19] are 5.0 wt%. It is attributed to the enhanced Seebeck effect of samples when CNTs are doped with boron, while the thermal conductivity of expanded graphite and graphene is above that of CNTs, resulting in enhanced thermoelectric properties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples prepared with borondoped carbon nanotubes have the highest ZT value, 3.3 times the 5.0 wt% content of the samples prepared by the original CNTs. The higher ZT values of boron-doped CNTs cement matrix composites when the content of CNTs, [13,14,29] EG, [15,83] and reduced graphene oxide (RGO) [19] are 5.0 wt%. It is attributed to the enhanced Seebeck effect of samples when CNTs are doped with boron, while the thermal conductivity of expanded graphite and graphene is above that of CNTs, resulting in enhanced thermoelectric properties.…”
Section: Resultsmentioning
confidence: 99%
“…[10,11] Chung et al showed that the Seebeck coefficient of cement paste with the addition of 1.0 wt% steel fibers increased from 2.0-67.9 μV K À1 . [12] After 2011, nanoscale materials, as well as nanometal oxides, were added to cement-based materials such as CNTs, [13,14] expanded graphite(EG), [15,16] graphene nanosheets (GNP), [17][18][19][20][21] and metal oxides (e.g., Fe 2 O 3 , [22] ZnO) [2] to increase the thermoelectric properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature reviewed above, most of the reports are centered on experiments and tests conducted on TEG because of TEG's excellent thermoelectric properties and low cost. Thermoelectric cementitious composites have even shown good thermoelectric properties as reported in recent years 104,105 . In particular, researchers in reducing the carbon content still maintain excellent thermoelectric properties for improving the mechanical properties of thermoelectric cement matrix 106,107 .…”
Section: Integrated Use Of Thermoelectric Technology In Pavement Ener...mentioning
confidence: 93%
“…Thermoelectric cementitious composites have even shown good thermoelectric properties as reported in recent years. 104,105 In particular, researchers in reducing the carbon content still maintain excellent thermoelectric properties for improving the mechanical properties of thermoelectric cement matrix. 106,107 However, the practical application of thermoelectric cementitious composites is still in the exploratory stage.…”
Section: Integrated Use Of Thermoelectric Technology In Pavement Ener...mentioning
confidence: 99%